Hermeneutika Praktis Dalam Pendidikan Iman di Indonesia: Sebuah Kritik Terhadap Pendekatan Kontekstual dan Implikasinya Bagi Katekese Umat - Habur, Agustinus Manfred (Riviera Publishing, 2025)
Catechesis, as a contextual faith education, in Indonesia is realized through the Catechesis of the Ummah, which emphasizes social analysis in the light of faith with a practical hermeneutic approach. This approach directs faith education to the act of liberation from injustice. Although successful in involving the people in society, this approach tends to be pragmatic and does not pay attention to the transcendental dimension of faith, namely communion with God. This study aims to evaluate practical hermeneutic approaches in the Catechesis of the Ummah in Indonesia, identify its impact on the appreciation of faith, and offer a more balanced hermeneutic alternative. Through literature review and qualitative content analysis of Church documents, academic works, and pastoral experiences, the research found the dominance of practical hermeneutics, the tendency of the Bible as a moral guide, the lack of faith transformation, and ideally the Ecclesiastical Base Community (KBG) as a forum for catechesis. In conclusion, in order to guarantee a balance of practical and transcendental dimensions, practical hermeneutics needs to be combined with post-hermeneutics. Post-hermeneutics emphasizes the role of the Word of God as a divine revelation that leads to the transformation of life and encourages a personal encounter with Christ, the primary goal of faith education.